Pathogenic Leptospira Species Are Present in Urban Rats in Sydney, Australia - Miguel A. Bedoya-Pérez; Mark E. Westman; Max Loomes; Nga Yee Natalie Chung; Benjamin Knobel; Michael P. Ward (Microorganisms, 2023)
Leptospirosis is an emerging disease among people and dogs in Sydney, Australia. However, the routes of Leptospira transmission in these cases, and in particular the possible role of rats as reservoirs of infection in Sydney, are unknown. Rats were collected within the City of Sydney Council area and their kidneys were tested for pathogenic Leptospira DNA by real-time (q)PCR. A subset of rats also had qPCR testing performed on whole blood and urine, and Microscopic Agglutination Testing (MAT) that included a panel of 10 Leptospira serovars from nine different Leptospira serogroups was performed on a subset of serum samples. Based on qPCR testing, the proportion of rats with Leptospira DNA in their kidneys was 9/111 (8.1%). qPCR testing of blood samples (n = 9) and urine (n = 4) was negative. None of the 10 serum samples tested MAT positive. A primary cluster of qPCR-positive locations was detected based on six infected rats, which partially overlapped with a previously identified cluster of canine leptospirosis cases in Sydney. These findings suggest that rats in Sydney might play a role in the transmission of leptospirosis to dogs and people. Further testing of rats in Sydney and investigation into other possible wildlife reservoirs of infection and environmental sources of leptospires are needed.